ANTESEDEN DAN KONSEKUENSI CUSTOMER ENGAGEMENT PADA KONSUMEN GENERASI Z (Studi Kasus E-commerce Tokopedia Indonesia) - Dewi Asiyah Rahayu; Muhammad Syahrul Ramadhan; Rachma Diani (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to analyze and provide empirical evidence of the influence of brand experience, namely sensory and affective brand experience as antecedent factors of customer engagement, and their consequences on brand loyalty. Data was collected using an online questionnaire with a sample of 116 respondents. The data was processed using the SEM - Amos analysis method. The results show that affective brand experience has a positive effect on customer engagement and there is a positive influence on customer engagement on brand loyalty. However, no influence was found on sensory brand experience on customer engagement. This research is limited by 3 things, one of which is respondents who only focus on e-commerce Tokopedia Indonesia users from generation Z who live in Jakarta with an age range of 18-24 years, so it is difficult to be generalized